Effect of harvesting technique on recovery rate and in vitro development of caprine follicular oocytes for in vitro procedures* - UMA MAHESH, Y; MUTHA RAO, M; SAMBASIVA RAO, K R S (The Indian Journal of Animal Sciences, 2013)
The present study was aimed at assessing efficacy of 3 harvesting methods on the quantity and quality of oocytes recovered for assisted reproduction procedures in goat. The average total number of oocytes recovered per ovary was significantly higher by slicing (6.54±0.39) and puncture (6.59±0.39) than by the aspiration method (4.09±0.19). However, the percentage of good quality oocytes was higher in the puncture method (71.56%), compared to the aspiration (71.27%) or slicing (61.61%) methods. The oocyte recovery was significantly lower in CL containing ovaries than that of ovaries without CL in aspiration (2.92 vs 4.57), puncture (5.89 vs 6.78) and slicing (5.40 vs 7.02) methods. However, the presence of CL did not affect the oocytes ability to reach the MII stage (75.31% vs 76.67%). The side (right or left) of the ovary not showed any significant effect on mean of total oocyte recovery and other grades of oocytes. However the large sized ovaries were yielded significantly higher number of oocytes than smaller ovaries. The results showed that the rates of COCs that reached the metaphase-II (M-II) stage were 79.88, 78.09 and 72.63% in aspiration, puncture and slicing techniques, respectively. The maturation rate was significantly lower in slicing method. The oocytes obtained were matured and parthenogenetically activated in vitro using ionomycin and 6-DMAP. There was no significant difference in the subsequent percentage of cleavage and development to blastocyst stage in vitro between the three methods of oocyte harvesting. It was concluded that though oocyte recovery, and in vitro developmental rates did not vary significantly between puncture and slicing methods, yet puncture method was found to be superior due to low debris content and recovery of more number of culture grade oocytes. Oocyte recovery by aspiration from small sized ovaries was difficult due to less number of visible follicles. Puncture method can be used as an alternative to slicing and aspiration for oocyte recovery in goat.